Creation of a zymogen - Parit Plainkum (2018)
Cells produce proteases as inactive zymogens. Here, we demonstrate that this tactic can extend beyond proteases. By linking the N and C termini of ribonuclease A, we obstruct the active site with the amino acid sequence recognized by plasmepsin II, a highly specific protease from Plasmodium falciparum. We generate new N and C termini by circular permutation. In the presence of plasmepsin II, a ribonuclease zymogen gains ∼103-fold in catalytic activity and maintains high conformational stability. We conclude that zymogen creation provides a new and versatile strategy for the control of enzymatic activity, as well as the potential development of chemotherapeutic agents.